(untitled) (Berlin, 2008)
Biotechnology offers one of the most economical and environmentally benign methods of air pollution control for industrial and municipal airstreams. Volatile organic and inorganic odorous compounds from various industries are emitted in large quantities and create hazards to the ecosystem and health effects to humans. Thus, the demand for odor and air pollution control systems that provide nuisance-free, breathable air is constantly growing.
Keywords: Bioremediation,Odor control,Air quality management,Xử lý sinh học,Kiểm soát mùi,Quản lý chất lượng không khí